2016
DOI: 10.1177/1550059416632413
|View full text |Cite
|
Sign up to set email alerts
|

Wake and Sleep EEG in Patients With Huntington Disease

Abstract: The aim of the study was to evaluate the EEG modifications in patients with Huntington disease (HD) compared with controls, by means of the exact LOw REsolution Tomography (eLORETA) software. We evaluated EEG changes during wake, non-rapid eye movement (NREM) and rapid eye movement (REM) sleep. Moreover, we reviewed the literature concerning EEG modifications in HD. Twenty-three consecutive adult patients affected by HD were enrolled, 14 women and 9 men, mean age was 57.0 ± 12.4 years. Control subjects were he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…Several potential biomarkers appear to replicate across human studies. One of the most replicable findings was an increase in absolute delta power, which has been reported frequently in HD subjects (42, 44, 45, 47, 49) although not in premanifest subjects (41, 43, 46). In premanifest HDGECs, the relative power of specific sub-bands has been observed to be decreased across multiple studies (4144, 46, 47, 49).…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Several potential biomarkers appear to replicate across human studies. One of the most replicable findings was an increase in absolute delta power, which has been reported frequently in HD subjects (42, 44, 45, 47, 49) although not in premanifest subjects (41, 43, 46). In premanifest HDGECs, the relative power of specific sub-bands has been observed to be decreased across multiple studies (4144, 46, 47, 49).…”
Section: Discussionmentioning
confidence: 69%
“…Delta LORETA power was higher in HD relative to controls during wake in both studies. While both studies have other results of interest, there was no overlap in other findings, as Piano et al (42) found no other differences in HD relative to controls during wake, and Painold et al (44) did not examine NREM and REM states.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations